Knowledge and Attitudes Relating to Women's Rights to Land Ownership - Lilian Oryema; Colbert ZZiwa Tamale; Brian Makabayi (African Journal on Land Policy and Geospatial Sciences)
Context and background In many societies including Uganda, land ownership is intricately linked to power, identity, and socio-economic status. Despite legal reforms, women in Africa, particularly Uganda, face discrimination and barriers in land ownership due to sociocultural norms and implementation gaps which has caused a problem of low numbers of women engaged in matters of their rights to land ownership yet women’s rights to land ownership are very important in the development of the country given their role in agriculture and the role they play in society. Goal and Objectives: The research sought to evaluate the knowledge and attitudes of women in Kakunyu Village concerning their land ownership rights by assessing the level of knowledge and attitude of women on their rights to ownership of land and also investigate perceived factors that affect women’s rights to land ownership. Methodology: Questionnaires and interviews were used to collect data and the data was analyzed using descriptive statistics and NVivo 14 for thematic analysis. Results: The research found that: majority of the women were not aware of specific legal provisions for land ownership, Cultural norms heavily influenced attitudes of land ownership, traditional practices and legal complexities were key barriers to women land ownership. The study recommended the need for targeted policy interventions, increased legal literacy, and community-driven initiatives to promote gender equity in land ownership.